Статистика цукрового діабету у дітей в Україні (аналіз і прогноз) - Зелінська, Н. Б.; Глоба, Є. В.; Погадаєва, Н. Л. (Clinical Endocrinology and Endocrine Surgery, 2013)
The results of the analysis of the prevalence and incidence of diabetes among children in Ukraine for the past 5 years are given. Marked dynamics of disease progression in children of different age groups, especially – at the age of 0-6 years, and the highest incidence of the disease among children of industrial regions.